Studying Snow Failure With Fiber Bundle Models - Capelli, Achille; Reiweger, Ingrid; Schweizer, Jürg (Frontiers in Physics, 2020)
Snow is a highly porous material with properties that may strongly differ depending on the environmental conditions. On slopes, the layered snowpack may fail and avalanches occur. Hence, knowing how snow deforms and fails is essential for understanding and modeling snow avalanche release and flow. The response of snow to imposed load or deformation and the failure behavior depends on the rate of the applied load or of displacement and follows from the complex, foam like, microstructure of snow and the properties of ice. The mechanical response and failure of snow can well be captured with fiber bundle models (FBM). We review the use of FBMs for studying snow failure. In particular, we show how FBMs have been used for studying the micromechanical processes, such as ice sintering and viscous deformation, to reproduce the results of snow failure experiments. Moreover, FBMs can reproduce signatures of acoustic emissions (AE) preceding snow failure, ease the AE interpretation, and shed light on the underlying progressive failure process.